M‐EA (methotrexate, etoposide, dactinomycin) and EMA‐CO (methotrexate, etoposide, dactinomycin / cyclophosphamide, vincristine) regimens as first‐line treatment of high‐risk gestational trophoblastic neoplasia. Issue 9 (4th December 2020) - Singh, Kam; Gillett, Sarah; Ireson, Jane; Hills, Anne; Tidy, John A.; Coleman, Robert E.; Hancock, Barry W.; Winter, Matthew C.
Abstract: High‐risk gestational trophoblastic neoplasia (GTN) is highly chemosensitive with an excellent prognosis with treatment. Historically in the United Kingdom, the high‐risk regimens used have been M‐EA (methotrexate, etoposide, dactinomycin) (Sheffield) and EMA‐CO (methotrexate, etoposide, dactinomycin / cyclophosphamide, vincristine) (Charing Cross, London) with prior published data suggesting no difference in survival between these. Our Sheffield treatment policy changed in 2014, switching from M‐EA to EMA‐CO, aiming to reduce time in hospital, and harmonise UK practice. We aimed to report the toxicities, response rates and survival outcomes for 79 patients with high‐risk GTN treated in the first‐line setting with either M‐EA (n = 59) or EMA‐CO (n = 20) from 1998 to 2018. Median duration of treatment was similar (M‐EA, 17.3 weeks (IQR 13.9‐22.6) and 17.6 weeks (IQR 13.4‐20.7) with EMA‐CO. For M‐EA, overall human chorionic gonadotrophin (hCG) complete response (CR) rate was 84.7% (n = 50/59). Two patients died of drug‐resistant disease after several lines of multiagent chemotherapy; overall survival is 96.6% (median follow‐up 10.4 years). For EMA‐CO, overall hCG CR rate was 70%, overall survival is 100% (median follow‐up 4 years). In our experience, patients treated with EMA‐CO experienced an apparent increased incidence of neutropenia, non‐neutropenic Grade 3‐4 infection, peripheral neuropathy and more treatment delays and nights in hospital. Granulocyte‐colony stimulating factor, after both EMA and CO arms, titrated to baseline neutrophil count improved the toxicity profile. Both treatment regimens are associated with excellent prognosis; selection of regimen may be further guided by individual patients' personal, social and family circumstances. There is further rationale to explore whether these regimens can be refined, such as 2‐weekly EMA, to optimise patient experience and reduce toxicity while maintaining efficacy. Abstract : What's new? High‐risk gestational trophoblastic neoplasia (GTN) is highly sensitive to chemotherapy and has excellent prognosis. However, different treatment approaches can impact toxicities, travel requirements, and time spent in hospitals. Here, outcome and patient experience were investigated for two chemotherapeutic regimens, M‐EA (methotrexate, etoposide, dactinomycin) and EMA‐CO (methotrexate, etoposide, dactinomycin /cyclophosphamide, vincristine), employed at the Sheffield GTN treatment center. Survival for high‐risk GTN patients treated with M‐EA or EMA‐CO was over 95 percent. Differences in scheduling, in‐patient requirements, and toxicities were observed, suggesting that patients' personal, social, and family circumstances should be considered in order to optimize individual care.